Japanese traditions in the development of Changchun in the early 20th century - Bazilevich, Mikhail; Tceluiko, Dmitry (project baikal, 2025)
The article reflects the intermediate results of the study conducted by the authors under the grant of the Russian Science Foundation “Methods of integration of zones of historical development and preservation of cultural heritage sites in the conditions of development of modern cities of northeastern China”. The authors consider the results of the activities of Japanese architects and engineers who worked in Changchun in the early 20th century. The authors also identify a number of historical and cultural heritage sites and their significance in the general process of forming the image of the city.
Keywords: Changchun; tatsuno; style; architecture; heritage